Processing of Polyvinyl Acetate Phthalate in Hot-Melt Extrusion-Preparation of Amorphous Solid Dispersions - Marius Monschke; Kevin Kayser; Karl G. Wagner (MDPI AG, 2020)
The preparation of amorphous solid dispersions (ASDs) is a suitable approach to overcome solubility-limited absorption of poorly soluble drugs. In particular, pH-dependent soluble polymers have proven to be an excellently suitable carrier material for ASDs. Polyvinyl acetate phthalate (PVAP) is a polymer with a pH-dependent solubility, which is as yet not thoroughly characterized regarding its suitability for a hot-melt extrusion process. The objective of this study was to assess the processability of PVAP within a hot-melt extrusion process with the aim of preparing an ASD. Therefore, the influence of different process parameters (temperature, feed-rate) on the degree of degradation, solid-state and dissolution time of the neat polymer was studied. Subsequently, drug-containing ASDs with indomethacin (IND) and dipyridamole (DPD) were prepared, respectively, and analyzed regarding drug content, solid-state, non-sink dissolution performance and storage stability. PVAP was extrudable in combination with 10% (w/w) PEG 3000 as plasticizer. The dissolution time of PVAP was only slightly influenced by different process parameters. For IND no degradation occurred in combination with PVAP and single phased ASDs could be generated. The dissolution performance of the IND-PVAP ASD at pH 5.5 was superior and at pH 6.8 equivalent compared to commonly used polymers hydroxypropylmethylcellulose acetate succinate (HPMCAS) and Eudragit L100-55.